COVID-19 ICU Visiting and Family Communication in End of Life Patients: HPUPM Experience - Azahar, Aizad; Ibrahim, Noor Airini; Mohd Idris, Siti Nur Izzati (International Journal of Human and Health Sciences (IJHHS), 2022)
The current pandemic has set most healthcare centres to prohibit visits. This is mainly due to the limited knowledge about disease transmission, protection against transmission and the scarcity of personal protective equipment (PPE). Thus, we solely used phone and video calls as a method to maintain communication with the next of kin. To be visited by loved ones is among the important aspects of ‘humanising’ an intensive care unit (ICU). Often, we tend to overlook the perspective of being a patient and the need of the next of kin. Insecurity, feeling of isolation and unfamiliarity will bring about many potential negative sequelae, more so in patients approaching the end of life. The presence of loved ones by the bedside will bring about better closure, transparency and a better understanding of any decisionmaking process and grief. The poster is aimed to share our view and experience in permitting next of kin visit into HPUPM COVID-19 ICU. We believe that our ICU is one of the first few centres in Malaysia that permits such visits, targeting especially patients in their end of life. Since July 2021, 17 patients with the median age of 50 years have had the opportunity for such visits. They had a median stay of 14 days in ICU. Phone interviews were conducted to identify t the next of kin with regards to their age, premorbid and vaccination history. Only healthy visitors from the range of 18 to 65 years, completed two doses of vaccination, or completed a period of home quarantine could enter. Briefing on the sequence of PPE donning and doffing, safety protocols and visiting etiquette were done by a trained critical care nurse. No limitation of hours was set during the visit. Subjectively, next of kin expressed better satisfaction with their visits as compared to getting an update via calls. However, we are still in the midst of structuring a qualitative study on satisfaction based on the data that we had collected for this protocol. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S28